Definition of the functional approach for an Agricultural Projects Office in an academic research center - Mora Valverde, David (2019)
A characterization of the organizational structure and the main processes of a center dedicated to developing research projects in the agricultural area was carried out, with the objective of establishing a reference framework that facilitates the definition and eventual implementation of a project office adaptable to his academic work.